Strategic Management Methods in Islamic Economics and Finance Research - Luthfiana, Alda (SMART Insight, 2023)
This study tries to review the application of research using the Strategic Management method in the theme of Islamic economics and finance. It uses descriptive statistical analysis based on selected 72 article publications. The entire sample publications have published from 2007 to 2019. The data is then processed and analyzed into 4 clusters using the VOSviewer application program to find out the bibliometric map of research development in the field of strategic management indexed by Scopus. The results show that research using the Strategic Management method is still dominated by Islamic banking followed by Halal Industry, and Islamic microfinance. The rest are issues about waqf, BMT, Islamic Finance, Islamic Economic Development, Sharia Compliance. Indonesia, Malaysia and Iran are the 3 countries with the most study areas compared to other countries. The most widely used method is the SWOT Analysis, IFE EFE method, Delphi Method, QSPM Method